ACQUISITION OF LANGUAGE POLITENESS AMONG ACADEMIC COMMUNITY IN SMA 6 YOGYAKARTA: PSYCHOPRAGMATICS CASE STUDY: PEMEROLEHAN KESANTUNAN BERBAHASA KELUARGA SMAN 6 YOGYAKARTA: STUDI KASUS PSIKOPRAGMATIK - Pranowo Pranowo; Veronika Endang Wahyuni (Jurnal Kata, 2022)
This article is a qualitative descriptive case study. The purpose of this study is to describe the greeting by the speaker to the speech partner, the process of acquiring politeness, and obtaining the pragmatic meaning of politeness. The research method includes data sources from teachers, students, and parents who often visit the school. The data of the research data is speech uttered by fellow teachers, students with teachers, and teachers with guardians of students. The research findings include (a) greetings between teachers, students, and student guardians are generally polite, (b) the process of language acquisition usually occurs through habituation, and (c) pragmatic meanings found in general are to ask, greet, inform, and rebuke.